solex1sample

−→ pr = vextendsingle vextendsingle vextendsingle

Info iconThis preview shows pages 10–13. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: −→ PR = vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle hatwide ı hatwide hatwide k − 3 2 − 1 1 − 1 1 vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle = (2 − 1) hatwide ı + (3 − 1) hatwide + (3 − 2) hatwide k = hatwide ı + 2 hatwide + hatwide k The correct answer is (E) . Solution of problem 1.3: If −→ F = −→ a + −→ b with −→ a || −→ v and −→ b ⊥ −→ v , then −→ a is the orthogonal projection of −→ F onto −→ v . From the formula for an orthogonal projection we compute −→ a = proj −→ v −→ F = −→ F · −→ v | −→ v | −→ v = ( 2 , 1 , − 3 ) · ( 3 , − 1 , ) 3 2 + ( − 1) 2 ( 3 , − 1 , ) = 5 10 ( 3 , − 1 , ) = (bigg 3 2 , − 1 2 , )bigg . Therefore −→ b = −→ F − −→ a = ( 2 , 1 , − 3 ) − (bigg 3 2 , − 1 2 , )bigg = (bigg 1 2 , 3 2 , − 3 )bigg . 10 The correct answer is (B) . square Solution of problem 1.4: If we label the points on the plane as P = (1 , 2 , 0), Q = (2 , 2 , 1), and R = (0 , 1 , 1), then we can easily write two vectors parallel to the plane, e.g. vectoru = −−−→ P Q = (2 − 1) hatwide ı + (2 − 2) hatwide + (1 − 0) hatwide k = hatwide ı + hatwide k vectorv = −−−→ P R = (0 − 1) hatwide ı + (1 − 2) hatwide + (1 − 0) hatwide k = − hatwide ı − hatwide + hatwide k . The normal vector to the plane is given by the cross-product vector n = vectoru × vectorv . We compute vector n = vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle hatwide ı hatwide hatwide k 1 1 − 1 − 1 1 vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle = hatwide ı − 2 hatwide − hatwide k . Thus a point P = ( x, y, z ) on the plane must satisfy the equation vector n · −−→ P P = 0, which is ( x − 1) − 2( y − 2) − ( z − 0) = 0 or simply x − 2 y − z = − 3 . Substituting the various choices in this equation we see that the only solution is the point (2 , 1 , 3) corresponding to answer (F) . Solution of problem 1.5: The curvature of −→ r ( t ) is given by κ ( t ) = vextendsingle vextendsingle vextendsingle d −→ T dt vextendsingle vextendsingle vextendsingle | −→ r ′ | , where −→ T is the unit tangent vector. We compute −→ r ′ ( t ) = ( 2 , 2 t, ) , and so | −→ r ′ | = √ 4 + 4 t 2 . In particular we have −→ T = (Big 2(4 + 4 t 2 ) − 1 2 , 2 t (4 + 4 t 2 ) − 1 2 , )Big . 11 Substituting in the formula for the curvature we get κ ( t ) = vextendsingle vextendsingle vextendsingle d −→ T dt vextendsingle vextendsingle vextendsingle | −→ r ′ | = vextendsingle vextendsingle vextendsingle d dt (Big 2(4 + 4 t 2 ) − 1 2 , 2 t (4 + 4 t 2 ) − 1 2 , )Bigvextendsingle vextendsingle vextendsingle (4 + 4 t 2 ) 1 2 = vextendsingle vextendsingle vextendsingle (Big − 8 t (4 + 4 2 ) − 3 2 , 2(4 + 4 t 2 ) − 1 2 − 8 t 2 (4 + 4 2 ) − 3 2 , )Bigvextendsingle vextendsingle vextendsingle (4 + 4 t 2 ) 1 2 Evaluating at t = 0 we get κ (0) = |( , 1 , )| 2 = 1 2 ....
View Full Document

{[ snackBarMessage ]}

Page10 / 17

−→ PR = vextendsingle vextendsingle vextendsingle...

This preview shows document pages 10 - 13. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online